Establishing a new model for estimation of the control delay at priority junctions in Malaysia. Issue 1 (1st January 2018) - Ali Sahraei, Mohammad; Che Puan, Othman; Hosseini, Seyed Mehrshad Parvin; Almasi, Mohammad Hadi
Abstract: In analysis of priority junctions, control delays to minor street automobiles are often approximated utilizing the present mathematical models. Nevertheless, the applicability of such a technique depends on the basis and the source of the data with which the model was calibrated. This research was accomplished to establish control delays using Multi-Linear Regression (MLR) for left- and right-turning maneuver from minor road at priority junctions in suburban areas. The data were gathered at two priority junctions utilizing video recording method. In both movements, control delays to minor street automobiles increase as the volumeof main street traffic increases. The comparisons among observed control delays and the values estimated utilizing the Malaysia Highway Capacity Manual pointed out that; in general, the observed delays were not in a good agreement with the values computed by theoretical model especially within right turn from minor road. Additionally, the outcomes of this study revealed that the observed delays were in a well agreement with values predicted using the MLR's models for left and right turns. Such a finding signifies that new model is directly applicable to the evaluation of control delays at priority junctions in Malaysia.